2020
DOI: 10.2196/15335
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Survivors’ Receptiveness to Digital Technology–Supported Physical Rehabilitation and the Implications for Design: Qualitative Study

Abstract: Background Physical activity is associated with a positive prognosis in cancer survivors and may decrease the risk of adverse effects of treatment. Accordingly, physical activity programs are recommended as a part of cancer rehabilitation services. Digital technology may support cancer survivors in increasing their level of physical activity and increase the reach or efficiency of cancer rehabilitation services, yet it also comes with a range of challenges. Objecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 42 publications
3
11
0
2
Order By: Relevance
“…Many patients receiving active cancer treatment have associated toxicities that are known to impair short-term work ability [ 6 , 35 ], and these may not be immediately amenable to improvements in self-management. The results of this study complement other recent studies showing the receptiveness of cancer survivors to digital technology for the support of physical rehabilitation [ 36 , 37 ], along with demonstrated improvements in quality of life through digital support [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…Many patients receiving active cancer treatment have associated toxicities that are known to impair short-term work ability [ 6 , 35 ], and these may not be immediately amenable to improvements in self-management. The results of this study complement other recent studies showing the receptiveness of cancer survivors to digital technology for the support of physical rehabilitation [ 36 , 37 ], along with demonstrated improvements in quality of life through digital support [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…In the case of cancer patients, cutbacks were made to the prescription of guided and supervised physical exercise, and certain clinical procedures were suspended or delayed [ 15 , 16 ]. Some studies have shown the importance of designing group-based physical activity programmes to promote mental health and resilience in cancer survivors [ 17 , 18 ]. However, studies on breast cancer patients undergoing active treatment have focused on the prescription of physical exercise in person both individually and in small groups [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…An alternative cost-efficient means to provide guidance regarding physical exercise is via digital apps on tablet computers. As tablets are highly mobile, they can be conveniently used in locations that allow to exercise [ 12 - 16 ]. They have a screen of sufficient size for video-based instructions and most importantly, older people are more likely to use tablets than smartphones [ 17 ].…”
Section: Introductionmentioning
confidence: 99%